The Implementation of ClassPoint in Learning English: A Case Study of Students at State Islamic Senior High School Medan - Nikmah Fadillah Nasution; Rahmah Fithriani; Ahmad Amin Dalimunthe (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Using Information and Communication Technology (ICT) in schools improves the quality of teaching, especially now that we are in the Fourth Industrial Revolution.  This research examines the application of ClassPoint in instructing English to eleventh-grade students at State Islamic Senior High School Medan. A qualitative case study design was utilized, encompassing 37 students across three observation cycles within a three-month duration.  Data were collected via observation, interviews, and documentation and analyzed through data reduction, presentation, and conclusion-drawing methodologies.  The results showed that student engagement went up a lot, from 40.54% in Cycle I to 94.59% in Cycle III.  Students also said that they were more comfortable and effective at learning in each cycle.  The research indicates that incorporating interactive digital tools like ClassPoint can promote active learning, increase engagement, and elevate English language proficiency in secondary education environments.